2016
DOI: 10.1186/s12934-016-0435-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel esterase from a marine mud metagenomic library for biocatalytic synthesis of short-chain flavor esters

Abstract: BackgroundMarine mud is an abundant and largely unexplored source of enzymes with unique properties that may be useful for industrial and biotechnological purposes. However, since most microbes cannot be cultured in the laboratory, a cultivation-independent metagenomic approach would be advantageous for the identification of novel enzymes. Therefore, with the objective of screening novel lipolytic enzymes, a metagenomic library was constructed using the total genomic DNA extracted from marine mud.ResultsBased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 46 publications
6
35
0
1
Order By: Relevance
“…Lx-Est BAS ∆SP retained over 85% of its initial catalytic activity after storage for six weeks (4 • C), whereas the free enzyme lost~80% of its activity after only two weeks and lost almost all its activity in less than three weeks. These results clearly indicated that enzyme immobilization significantly increased storage stability, in line with another report [37].…”
Section: Effects Of Metal Ions and Detergents On Lx-est Bas ∆Sp And Fsupporting
confidence: 91%
“…Lx-Est BAS ∆SP retained over 85% of its initial catalytic activity after storage for six weeks (4 • C), whereas the free enzyme lost~80% of its activity after only two weeks and lost almost all its activity in less than three weeks. These results clearly indicated that enzyme immobilization significantly increased storage stability, in line with another report [37].…”
Section: Effects Of Metal Ions and Detergents On Lx-est Bas ∆Sp And Fsupporting
confidence: 91%
“…The CAP domain is highlighted in red, the catalytic triad Ser144, Glu238, and His268 is highlighted in magenta, the oxyanion hole comprising of residues Gly76 and Gly77 is highlighted in yellow, the catalytic domain is highlighted in light blue. an important role in marine carbon degradation and cycling, and given that a functional metagenomics based approach had previously been successfully employed to identify the E40 esterase from sediment from the South China Sea (Li et al, 2012;Li P. Y. et al, 2015), and that marine sponge and sediment metagenomics libraries had resulted in the discovery of a variety of novel lipases including the recent reports of a cold-active salt tolerant esterase from artic sediment (De Santi et al, 2016); and a high organic solvent tolerant and thermostable esterase from marine mud (Gao et al, 2016); we targeted the metagenome of the deep sea sponge S. normani in an attempt to increase the repertoire of marine derived halophilic esterases. To this end we succeeded in identifying a gene encoding a novel psychrophilic esterase (7N9) from the hormone sensitive lipase (Hsl) family IV following the functional screening of a S. normani metagenomic library.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of microbial lipases and their industrial applications have been reviewed by Verma et al (2012). A large set of microbial lipases has been successfully identified using metagenomics, which is a cultivation-independent approach, and targets samples from extreme environments (Kim et al 2004;Barriuso et al 2013;Gao et al 2016). …”
Section: Microbial Lipid-degrading Enzymesmentioning
confidence: 99%
“…Next-generation sequencing technologies have allowed the sequencing of entire microbial genomes and metagenomics from particular environments, such as activated sludge and marine mud (Kim et al 2004;Ranjan et al 2005;Liaw et al 2010;Barriuso et al 2013;Gao et al 2016). These molecular genomics applications have permitted the analysis of sequencing data to identify target enzymes with specific functionalities for industrial interest.…”
Section: Homology-based Mining Of Lipase Genesmentioning
confidence: 99%
See 1 more Smart Citation